The potential of applying blockchain technologies in various sectors of the digital economy - Слатвінська, Валерія Миколаївна; Slatvinska, Valeriia M.; Milashovska, Olha; Korolovych, Oksana; Smyrnova, Nataliia (My University, 2022)
The objective of the article is to determine the potential of blockchain technologies in various sectors of the digital economy, in the case of the countries of the European Union. Methodology. The research assesses the use of digital technologies to ensure the country's digital development, based on data from the European Commission and the Digital Economy and Society Index (DESI). On the basis of DESI, a cluster diagram was created to determine the potential for the use of blockchain technology in the countries of the European Union. Results. The potential for the use of blockchain technology in each country depends and is significantly connected with the introduction of different technologies and the availability of the Internet, the provision of digital services by the government, the development of human capital. The main potential advantages of the technology include the following: acceleration of globalization processes, ensuring the country's transition from real production to technological development, change of established business models, transformation and optimization of value chains of different sectors of the economy by reducing costs; transformation of the nature of mediation due to technological changes; the use of cryptocurrency to achieve the consensus of economic agents on the allocation of scarce resources on a global scale.

El objetivo del artículo es determinar el potencial de las tecnologías blockchain en varios sectores de la economía digital, en el caso de los países de la Unión Europea. Metodología. La investigación evalúa el uso de tecnologías digitales para asegurar el desarrollo digital del país, basándose en los datos de la Comisión Europea y el Índice de Economía y Sociedad Digital (IESD). Sobre la base de IESD, se creó un diagrama de clúster para determinar el potencial de uso de la tecnología blockchain en los países de la Unión Europea. Resultados. El potencial de uso de la tecnología blockchain en cada país depende y está significativamente conectado con la introducción de diferentes tecnologías y la disponibilidad de Internet, la provisión de servicios digitales por parte del gobierno, el desarrollo del capital humano. Las principales ventajas potenciales de la tecnología incluyen las siguientes: aceleración de los procesos de globalización, asegurando la transición del país de la producción real al desarrollo tecnológico, cambio de modelos de negocio establecidos, transformación y optimización de cadenas de valor de diferentes sectores de la economía mediante la reducción de costos; transformación de la naturaleza de la mediación debido a cambios tecnológicos; el uso de la criptomoneda para lograr el consenso de los agentes económicos sobre la asignación de recursos escasos a escala global.

Метою статті є визначення потенціалу блокчейн-технологій у різних сектори цифрової економіки, у випадку країн Європейського Союзу. Методологія. Це дослідження оцінює використання цифрових технологій для забезпечення цифрового розвитку країни, на основі даних Європейської Комісії та Індексу цифрової економіки та суспільства (IESD). На основі IESD була створена кластерна діаграма для визначення потенціалу для використання технології блокчейн в країнах Європейського Союзу. Результати. Потенціал використання технології блокчейн у кожній країні залежить і суттєво пов’язане З впровадженням різних технологій і доступністю Інтернету надання цифрові послуги уряду, розвиток людського капіталу. Головний До потенційних переваг технології можна віднести: прискорення процесів о глобалізація, що забезпечує перехід країни від реального виробництва до розвитку технології, зміна усталених бізнес-моделей, трансформація та оптимізація ланцюжки вартості різних секторів економіки за рахунок зниження витрат; трансформація природи медіації внаслідок технологічних змін; використання криптовалюта для досягнення консенсусу економічних агентів щодо розподілу обмежені ресурси в глобальному масштабі.
Slatvinska V. M. The potential of applying blockchain technologies in various sectors of the digital economy / V. M. Slatvinska, О. Milashovska, N. Liba, O. Korolovych, N. Smyrnova // Revista de la Universidad del Zulia, 3ª época, Año 13, N° 36, 2022. - P. 288-304.
Keywords: digital technology; digitization; Information and Communication Technologies; Economy; tecnología digital; digitalización; Tecnologías de la Información y Comunicación; Economía; цифрові технології; оцифрування; Інформаційно-комунікаційні технології; Економіка; Research Subject Categories::TECHNOLOGY